CRITICAL STUDY OF OPTIMIZATION OF ISLAMIC CORPORATE GOVERNANCE IMPLEMENTATION TO ACHIEVE COMPANY PERFORMANCE - Reza Widhar Pahlevi (Universitas Agung Podomoro, 2019)
Guidelines for Good Corporate Governance an Islamic perspective have a broader context, do notseparate roles and responsibilities in all stakeholders actions under the auspices of Islamic sharia law.There are differences in concepts and perspectives between western perspective (Anglo Saxon andEuropean) Good Corporate Governanceand Islamic perspectives. The difference in the very basic pointof view that Good Corporate Governance is the Islamic perspective comes from tawhid, shari'ah, andthe concept of shura. Islamic Good Corporate Governance guidelines focus on the role of stakeholdersrelated to the company.The development of science that occurs in the perspective of Good Corporate Governance begins onthe basis of agency theory which states that there is a separation between ownership and managementthat has the potential to cause agency problems, ways to overcome agency problems through theimplementation of Good Corporate Governance. Implementation of guidelines for Good CorporateGovernance is an obligation for the company. This is more aimed at the existence of responsibility tothe public (public accountability) relating to the company's operational activities and it is expected thatthe company can comply with the provisions outlined in a positive law. In addition, this is related tothe level of compliance of sharia with sharia principles as described in the Qur'an, Hadith, and Ijma 'ofthe Ulama. Research related to Good Corporate Governance in the Islamic perspective with theachievement of company performance is expected to provide an overview of the Good CorporateGovernance framework that recognizes the rights of stakeholders as determined by law and encouragesactive cooperation between companies and stakeholders to create employee welfare, performance, andcorporate sustainability.